Adsorptive removal of cyanide from coke oven wastewater onto zero-valent iron: Optimization through response surface methodology, isotherm and kinetic studies. (20th March 2018) - Tyagi, Megha; Rana, Anu; Kumari, Soni; Jagadevan, Sheeja
Abstract: Lab scale studies were carried out to investigate the feasibility of employing zero-valent iron as a potential adsorbent for removal of cyanide from a synthetic coke oven wastewater. A response surface methodology called central composite design was employed to identify the most significant factors and optimize the effect of process parameters such as pH, dose of adsorbent and contact time on the adsorptive efficiency. Results showed that 98.98% removal of cyanide was obtained at pH of 9, adsorbent dose of 1.73 g/L after a contact time of 45 min for cyanide concentration of 50 mg/L. This study also reports the results of batch adsorption experiments, which includes the adsorption capacity, kinetics and isotherm of cyanide adsorption process. Langmuir and Freundlich equilibrium models were applied to determine the isotherm parameters. The equilibrium assessment illustrated that Langmuir isotherm model fitted with the adsorption data and a maximum cyanide adsorption capacity of 277.77 mg/g was achieved. The novel adsorbent (zero-valent iron) showed sorption capacity which is much higher than the maximum value reported in the literature for cyanide adsorption by other adsorbents such as activated carbon. The adsorption of cyanide onto zero-valent iron could be described by a pseudo-second order kinetic model, indicating chemisorption to be the mechanism of adsorption. This study demonstrates potential application of zero-valent iron for the removal of cyanide from recalcitrant industrial wastewater and could lead to novel approaches for remediation of cyanide in the environment. Graphical abstract: Image 1 Highlights: Optimization of process parameters for adsorption of cyanide on zerovalent iron. The zerovalent iron exhibited excellent adsorption capacity. Langmuir and Freundlich equilibrium models were applied. Kinetic modeling have been performed.